2016
DOI: 10.1016/j.jos.2016.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA-222 expression accelerates bone healing with enhancement of osteogenesis, chondrogenesis, and angiogenesis in a rat refractory fracture model

Abstract: Local administration of miR-222 inhibitor can accelerate bone healing by enhancing osteogenesis, chondrogenesis, and angiogenesis in the rat refractory model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
2
48
0
Order By: Relevance
“…Having demonstrated the inhibition of miR-222 promoted osteogenic and chondrogenic differentiation in vitro, miR-222 has been mixed with atelocollagen and administered in a rat refractory fracture model for in vivo bone healing assessment. [113] Bone union at the fracture site and enhanced capillary density was achieved in miR-222 inhibitor treated groups 8 weeks postimplantation. Overall, this study successfully demonstrated the effect of miR-222 knockdown on acceleration of bone healing by enhancing osteogenesis, chondrogenesis, and angiogenesis.…”
Section: Osteogenesis and Bone Repairmentioning
confidence: 88%
See 1 more Smart Citation
“…Having demonstrated the inhibition of miR-222 promoted osteogenic and chondrogenic differentiation in vitro, miR-222 has been mixed with atelocollagen and administered in a rat refractory fracture model for in vivo bone healing assessment. [113] Bone union at the fracture site and enhanced capillary density was achieved in miR-222 inhibitor treated groups 8 weeks postimplantation. Overall, this study successfully demonstrated the effect of miR-222 knockdown on acceleration of bone healing by enhancing osteogenesis, chondrogenesis, and angiogenesis.…”
Section: Osteogenesis and Bone Repairmentioning
confidence: 88%
“…[102,106] Whether one of the routes may be better suited for clinical translation remains to be elucidated, although in situ transfecting scaffolds hold greater potential to exist as "off-the-shelf" products. [107] Many distinct scaffold types have been tuned to serve the purpose of miRNA delivery, including several hydrogels, [58,92,106,[108][109][110][111][112][113][114] electrospun fibers, [63,[115][116][117][118] and more prolifically porous or spongy scaffolds. [46,47,50,54,55,96,112,[119][120][121][122][123][124][125][126][127][128][129][130] Before reviewing the details of their applications, summarized in Table 2 and described further in the next section, we will discuss the key characteristics making these materials amenable to miRNA delivery.…”
Section: Scaffolds For Microrna Deliverymentioning
confidence: 99%
“…miR‐222 is known to be a negative regulator of angiogenesis, a process critical to successful fracture repair. In conjunction with a rat femoral transverse fracture and cauterization of the periosteum at the fracture site, a miR‐222 inhibitor and mimic were each tested (along with a nonfunctional inhibitor negative control) for their effects on fracture repair . Initially, the miR‐222 inhibitor, mimic, and negative control were mixed with atelocollagen and administered into the fracture site (immediately after fracture).…”
Section: Mirnas and Fracture Repairmentioning
confidence: 99%
“…Enhanced hMSCs-mediated in vivo cartilage repair [32,60] miR-222 Enhanced chondrogenesis and osteogenesis of hMSCs in vitro. Improved angiogenesis and bone union and healing in vivo [102] circRNA-CER Increased expression of collagen II and aggrecan in human OA chondrocytes. Suppression of MMP13 [108] lncRNA-CIR Increased expression of collagen I, II, aggrecan and GAGs production in human OA chondrocytes.…”
Section: Silencing Of Non-coding Rnasmentioning
confidence: 99%
“…Notably, seeding of miR-221-depleted hMSCs in cartilage defects led to enhanced cartilage repair in vivo, providing a proof of concept for the implantation of miRNA-depleted hMSCs for improved cartilage repair. Interestingly, Yoshizuka et al showed that silencing of the paralogue of miR-221, miR-222, promoted chondrogenesis, and osteogenesis of hMSCs, as well as angiogenesis and bone healing in a rat fracture model [102].…”
Section: Silencing Of Non-coding Rnasmentioning
confidence: 99%